Excessive body weight and its contributing factors in visually impaired patients in northwest Ethiopia, 2024 - Ashenef, Baye; Yimenu, Bayu Wondimneh; Osman, Enatnesh Essa; Sinamaw, Derese; Baye, Gelagey; Teffera, Zigale Hibstu; Engida, Mamaru Getinet; Adugna, Adane; Mengistu, Enyew Fenta; Baylie, Temesgen; Jemal, Mohammed (Frontiers in Endocrinology, 2025)
BackgroundExcessive body weight are global health challenge affecting individuals across all age groups. They result from an imbalance between calorie intake and expenditure. Individuals with visual impairment are particularly vulnerable due to reduced physical activity, leading to higher rates of excessive body weight. This study assessed the prevalence and determinants of excessive body weight among visually impaired patients in northwest Ethiopia in 2024.MethodA multi-centered institution-based cross-sectional study was done with 384 visually impaired patients selected using a simple random sample technique. An interviewer-administered structured questionnaire and physical assessments were used to gather data. The crude and adjusted odds ratios, as well as the 95% confidence intervals, were calculated. Bivariate and multivariate logistic regression analyses were performed. Variables having a p-value < 0.05 were considered substantially associated with excessive body weight.ResultsThe prevalence of excessive body weight was 27.9% (95% CI: 23.2–32.8). Factors significantly associated with excessive body weight included being aged 65 or older (AOR = 5.43, 95% CI: 1.22–24.1), urban residency (AOR = 4.84, 95% CI: 2.95–7.95), and having visual impairment for five or more years (AOR = 3.33, 95% CI: 1.88–5.89).ConclusionExcessive body weight affects nearly one-third of visually impaired patients in northwest Ethiopia, with significant associations found for older age, urban residence, and long-term visual impairment. Integrating weight management programs, physical activity promotion, nutritional education, and community support is essential to improve health outcomes. Future studies using prospective cohort designs are recommended to explore causal relationships.